2005
DOI: 10.1021/jp044771r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Titanium Dioxide Nanoparticles with Mesoporous Anatase Wall and High Photocatalytic Activity

Abstract: Mesoporous titanium dioxide nanosized powder with high specific surface area and anatase wall was synthesized via hydrothermal process by using cetyltrimethylammonium bromide (CTAB) as surfactant-directing agent and pore-forming agent. The resulting materials were characterized by XRD, nitrogen adsorption, FESEM, TEM, and FT-IR spectroscopy. The as-synthesized mesoporous TiO2 nanoparticles have mean diameter of 17.6 nm with mean pore size of 2.1 nm. The specific surface area of the as-synthesized mesoporous na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
206
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(224 citation statements)
references
References 35 publications
11
206
0
7
Order By: Relevance
“…In turn, these findings suggested that the prepared S-and N-TiO2 photocatalysts could be effectively activated by visible-light irradiation. [19,21,22]. When compared with that of pure TiO2 previously reported by other researchers as well [23,24], the frequency was moved to a slightly lower wavelength for both types of the N-and S-TiO2.…”
Section: Surface Characteristics Of Photocatalystssupporting
confidence: 54%
See 2 more Smart Citations
“…In turn, these findings suggested that the prepared S-and N-TiO2 photocatalysts could be effectively activated by visible-light irradiation. [19,21,22]. When compared with that of pure TiO2 previously reported by other researchers as well [23,24], the frequency was moved to a slightly lower wavelength for both types of the N-and S-TiO2.…”
Section: Surface Characteristics Of Photocatalystssupporting
confidence: 54%
“…This frequency movement is likely due to the interaction between the doped N or S and H atoms [24,25]. The bands below 1,000 cm -1 are assigned to the titania crystal lattice vibration [21,22]. It is noteworthy that no distinct N-or S-associated peaks were observed for the FTIR results of the as-prepared photocatalysts.…”
Section: Surface Characteristics Of Photocatalystsmentioning
confidence: 93%
See 1 more Smart Citation
“…The most commonly used organic templates were amphiphilic poly(alkylene oxide) block copolymers, such as HO-(CH 2 CH 2 O) 20 (CH 2 CH(CH 3 )O) 70 ( 17 and cetyltrimethylammonium bromide (CTAB) ( Table 1). [29][30][31][32]43,[45][46][47]87,100 TiO 2 is an interesting material for photocatalytic applications and it is regarded as the most efficient and environmentally benign photocatalyst, and it has been most widely used for photodegradation of various pollutants such as methylene blue (MB), 30,37,52,55,57 methyl orange (MO), 30,39 Escherichia coli (E. coli), 57,60 Rhodamine B (RhB) 36,[46][47][48] Rhodamine 6G (Rh6G) 29 and phenol 27,47 (Table 1). The principle of the semiconductor photocatalytic reaction is straightforward.…”
Section: Synthetic Methods For Mesoporous Titania Photocatalystmentioning
confidence: 99%
“…In the FT-IR (Fig. S3), the peaks around 3430, 1630 and 1380 cm -1 could be attributed to the O-H stretching vibration and O-H bending of water molecules adsorbed onto the surface of the particles [33] , respectively. The broad band around 680 cm -1 observed was associated with TiO 2 crystal lattice vibrations [34,35] .…”
Section: Effect Of Reactant Concentration and Calcination Temperaturementioning
confidence: 99%